The Influence of Diet Menus and Sports Models on Decreased Blood Sugar Levels and Body Weight of Prediabetes Group - Enda Silvia Putri; Rina Wati; Dian Fera (Journal of Nutrition Science, 2020)
Prediabetes was a condition where a person has abnormal blood sugar levels but was not yet categorized as diabetes (140-199 mg / dl). The increased incidence of prediabetes affects the increasing number of cases of diabetes, unhealthy diet and irregular exercise models are factors that cause weight problems and blood sugar levels that increase cases of prediabetes to have an impact on diabetes cases. The research purpose was the effect of diet menus and exercise models on reducing blood sugar levels and body weight in the prediabetes group. The method research was the analytical method with the design of quasi-experimental, the population was 20 people, and the sample was total population or sample of 20 people by dividing 2 groups with different interventions, the technique with accidental sampling, and tool with SPSS 20, the data analyzed with independent t test. The result of research was the influence in group jasmine (diet and exercise menu (jogging)) (P value = 0.001 <α = 0.05), and in group rose (diet and exercise menu (casual walk)) (P value = 0.004 <α = 0.05) to reduce blood sugar levels and body weight. The conclusion of research was that the diet control and exercise menu models were able to influence the decrease in blood sugar levels and body weight in the prediabetes group, group a had a more significant effect because of jogging so that more calories burned.